2020
DOI: 10.5812/jjm.95713
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of katG, inhA, and ahpC in Isoniazid-Resistant Mycobacterium tuberculosis Clinical Isolates in Shanghai, China

Abstract: Background: Mycobacterium tuberculosis is a pathogen that causes Tuberculosis and can invade various organs in infected patients. Its high morbidity and high mortality seriously threaten human health. In recent years, the continuous emergence of drug-resistant Tuberculosis bacteria has brought severe challenges to the prevention and control of Tuberculosis. Objectives: This study aimed to characterize the most frequent mutations of the katG, inhA, and ahpC genes in isoniazid (INH)resistant M. tuberculosis clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…In our study, there were four cases of these mutations, which led to the phenotypic resistance being misjudged as susceptibility by nucleotide MALDI-TOF-MS. Similar to other studies, katG315 (86.8%, 70/91) was the most common isoniazid-resistance mutation site in this study, followed by inhA-15 (15.4%, 14/91) ( Cao et al, 2020 ;Smaoui et al, 2016 ;Vilchèze and Jacobs, 2014 ). Among the streptomycin-resistant isolates, mutations at codon 43 in rpsL were the most prevalent, but this mutation was also found in streptomycin-susceptible strains, and has been reported in other studies ( Sreevatsan et al, 1996 ;Wang et al, 2019 ;Wu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, there were four cases of these mutations, which led to the phenotypic resistance being misjudged as susceptibility by nucleotide MALDI-TOF-MS. Similar to other studies, katG315 (86.8%, 70/91) was the most common isoniazid-resistance mutation site in this study, followed by inhA-15 (15.4%, 14/91) ( Cao et al, 2020 ;Smaoui et al, 2016 ;Vilchèze and Jacobs, 2014 ). Among the streptomycin-resistant isolates, mutations at codon 43 in rpsL were the most prevalent, but this mutation was also found in streptomycin-susceptible strains, and has been reported in other studies ( Sreevatsan et al, 1996 ;Wang et al, 2019 ;Wu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Several other studies worldwide have demonstrated a similar trend of the prevalence of katG S315T mutations but with considerable geographical variations. The frequency of katG S315T mutation was reported in 65.4% of INH-R isolates in Australia [18], 71% in India [26], 63% in China [11], and 53.3% in Iran [8]. Furthermore, several systematic reviews reported a variation in the frequency of katG S315T mutations (64.2%) [27], 73.6% [28], and 95.8% [29].…”
Section: Discussionmentioning
confidence: 99%
“…[30]. The uneven occurrence of katG gene mutations may be primarily caused by variations in clinical pharmaceutical practices throughout nations and the limits of particular experimental strains [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation